(untitled) (Proceedings of the Institute of Biology, 2023)
Bacteriophages, which are viruses that infect bacteria, have a significant impact on the dynamics of bacterial communities, the evolution of bacterial genomes, and the biogeochemistry of ecosystems. The specific effects of these factors differ based on whether the phages establish lytic, chronic, or lysogenic infections. In this study, bacteriophages were isolated from wastewater samples obtained from the Central Wastewater Treatment Plant of Ulaanbaatar. The test strains of Escherichia coli NIM05 and Pseudomonas aeruginosa NIM09 from the collection of the Bacteriological Laboratory, the National Centre for Infectious Diseases were used to determine bacteriolytic activity of bacteriophages. Bacteriophages AT1 and AT2, demonstrating bacteriolytic activity, were isolated. Specifically bacteriophage AT1 was able to lyse 70.2% of cells from the total population of E. coli NIM05, while bacteriophage AT2 was able to lyse 78.5% of P. aeruginosa NIM09 within a 96-hour cultivation period. Bacteriophage titers were determined, resulting in 1.12 x 1010 PFU/m for the AT1 phage, and 0.98 x 1010 PFU/mL for the AT2 phage. Бохир уснаас ялган авсан фагийн бактериолитик идэвх Хураангуй. Бактерид халдварладаг вирус нь бактерийн өсөлтийн динамик, бактерийн геномын хувьсал, экосистемийн биогеохимийн процесст нөлөөлдөг. Эдгээр нөлөөллүүд нь тухайн фагууд литик, архагшсан эсвэл лизоген халдвар үүсгэж байгаа эсэхээс хамаарч өөр өөр байдаг. Энэхүү судалгаанд ХӨСҮТ –ийн Нэгдсэн лабораторийн Нян судлалын лабораторид хадгалагдаж байгаа Escherichia coli NIM05 болон Pseudomonas aeruginosa NIM09 –ийн омгуудыг тест өсгөврөөр ашиглав. Улаанбаатар хотын Төв цэвэрлэх байгууламжийн бохир уснаас эдгээр өсгөврийг лизист оруулах чадвартай АТ1 ба АТ2 бактериофагуудийг ялгаж авав. АТ1 бактериофаг E. coli –ийн нийт эсийн 70.2% –ийг, AT2 фаг P. аeruginosa –ийн нийт эсийн 78.5.5% –ийг 96 цагийн хугацаанд лизист оруулах чадвартай болохыг тогтоов. Ялгаж авсан AT1 фагийн титр 1.12x1010 PFU/mL, AT2 фагийн титр 0.98x1010 PFU/mL тус тус байна. Түлхүүр үгс: Бактериофаг, бактериолитик идэвх, бактери, E. coli, P. aeruginosa, бохир ус